Interaction Diagrams for Reinforced Concrete T-Columns - Asmaa Ahmad (Engineering and Technology Journal, 2005)
The present investigation gives a comprehensive theoretical study for the analysis of reinforced concrete T-columns under the simultaneous action of axial compressive load and uniaxial bending. A computer program is written which enables calculating the compressive and tensile forces together with their moments, and eventually gives the results in the form of design charts which can be used directly for design or analysis. In order to illustrate the use of the proposed design charts, four examples are given, two of which are design examples while the other two are analytsis.